Cancer and Thrombotic Risk: The Platelet Paradigm - Lee, Elizabeth C.; Cameron, Scott J. (Frontiers in Cardiovascular Medicine, 2017)
Hematologic malignancies and solid tumors increase the risk of venous and arterial thrombosis and contributing greatly to patient morbidity and mortality. Thrombosis occurs when the intricate balance of circulating blood clotting proteins and platelets is disrupted. In recent years, the interplay between paraneoplastic cells and platelets has become apparent, with a change in platelet phenotype causing dysregulated platelet activity. This review discusses mechanism of thrombosis in cancer, evidence for using drug therapy, and exciting research efforts to understand and hopefully control aberrant thrombotic events in patients with cancer.